A dictionary of zoology - Allaby, Michael; Allaby, Michael (New York : Oxford University Press, 1999)
"This is the most comprehensive and up-to-date dictionary of zoology available. Covering all aspects of the study of animals, and now fully revised for this new edition, it is ideal for students and will be invaluable to amateur naturalists." "Over 5,000 entries; wide coverage including animal behaviour, ecology, physiology, genetics, cytology, evolution, earth history, and zoogeography; full taxonomic coverage of arthropods, other invertebrates, fish, reptiles, amphibians, birds, and mammals; and new material on genetics, evolutionary studies, and mammalian physiology."--BOOK JACKET.
Rev. ed. of: Concise Oxford dictionary of zoology. 1991.
Also available online. Access restricted to registered users and institutions with site license agreements.
Keywords: Zoology -- Dictionaries; Zoologie -- Dictionnaires anglais